Skip to content
= λf.(λx.f(xx))(λ.xf(xx))
= λf.(λx.f(xx))(λ.xf(xx))



Block or Report

Block or report MichaelNeas

Block user

Prevent this user from interacting with your repositories and sending you notifications. Learn more about blocking users.

You must be logged in to block users.

Report abuse

Contact GitHub support about this user’s behavior. Learn more about reporting abuse.

Report abuse


  1. 🦉Public speaking and blogs

    Swift 27 10

  2. 🍎 developer docs flashcard app made with swiftUI

    Swift 6 2

  3. 🧪 Programming challenges, demos, and practice

    Swift 8

  4. Aviatodev 👩‍💻👨‍💻

    JavaScript 2 1

  5. hydra Public

    Open Source Prosthetic Arm 🦾

    Java 1 2

  6. mikeneas Public

    Personal Website 🏔


176 contributions in the last year

Jan Feb Mar Apr May Jun Jul Aug Sep Oct Nov Dec Jan Mon Wed Fri

Contribution activity

Seeing something unexpected? Take a look at the GitHub profile guide.